2018
DOI: 10.3126/tujm.v4i0.21672
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Pattern of Bacterial Pathogens of Enterobacteriaceae Family

Abstract: Objectives: This study was done to determine the drug resistance pattern and Extended Spectrum β-Lactamase (ESBL) in bacterial isolates of Enterobacteriaceae family from different clinical specimens.Methods: The isolates were identified by conventional culture techniques and subjected to antimicrobial susceptibility testing by modified Kirby Bauer disk diffusion methods and ESBL detection by combined disk method.Results: Of the total 1602 sample processed 200 (12.5%) bacteria of Enterobacteriaceae family were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…In the present study, a total of 204 bacterial isolates were obtained from 667 various clinical specimens. Among total isolates, Gram negative bacteria were predominant constituting 75.5% and Gram positive bacteria constituted 24.5%, which was in accordance with results of previous studies (Bhandari et al, 2016;Sah et al, 2017) suggesting predominance of Gram negative bacteria over Gram positive bacteria. Of all isolates, E. coli (31.4%) was the most prevalent bacteria followed by K. pneumoniae (27.5%).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, a total of 204 bacterial isolates were obtained from 667 various clinical specimens. Among total isolates, Gram negative bacteria were predominant constituting 75.5% and Gram positive bacteria constituted 24.5%, which was in accordance with results of previous studies (Bhandari et al, 2016;Sah et al, 2017) suggesting predominance of Gram negative bacteria over Gram positive bacteria. Of all isolates, E. coli (31.4%) was the most prevalent bacteria followed by K. pneumoniae (27.5%).…”
Section: Discussionsupporting
confidence: 91%
“…Of all isolates, E. coli (31.4%) was the most prevalent bacteria followed by K. pneumoniae (27.5%). Corroborating with the present study, several other studies have reported similar pattern of pathogens recovery from clinical specimens in Nepal and elsewhere (Akanbi et al, 2013;Ghimire et al, 2017;Sah et al, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…One disc each of ceftazidime (30μg) and cefotaxime (30μg) alone and one in combination ceftazidime and clavulanic acid (30/10μg) were placed at a distance of 20mm on a Muller Hinton agar plate inoculated with a bacterial suspension of 0.5 McFarland turbidity standards, and incubated overnight at 37°C. The ESBL-producing strains showed ≥5mm increase in zone diameter for either antimicrobial agent tested in combination with clavulanic acid versus its zone when tested alone [9,10,22] .…”
Section: Confirmatory Testmentioning
confidence: 97%
“…AmpC over production along with porin mutations of the outer membrane, can reduce susceptibility to carbapenems, in particular in plasmid mediated AmpC producers. [8,11,22] Porins are chemically selective and transport only one group of molecules and are specific for one molecule so the β-lactam and fluoroquinolone antibiotics they pass through porins to reach their targets in gram negative bacteria. Bacteria can develop resistance to these antibiotics by mutation of the gene that encodes the porin the antibiotics are then excluded from passing through the outer membrane resulting in multidrug resistance [8] .…”
Section: Detection Of Extended-spectrum Beta Lactamases and Ampc Betamentioning
confidence: 99%
“…Studies have reported that bacteremia caused by ESBL-producing Enterobacterales is associated with higher rates of treatment failure and patient mortality when compared to bacteremia caused by non ESBL-producing strains 1 , 25 . Various authors have emphasized that ESBL-producing Enterobacterales strains are not associated with resistance to ceftazidime-avibactam 6 , 7 , 10 , 15 , 25 , 26 , which was also demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%